Reformation of Syariah Judiciary Institution During COVID-19 Pandemic (INSLA E-Proceedings, 2020)
In Malaysia, the pandemic of coronavirus COVID-19 has impacted almost all areas of our life. The administration of the Syariah courts is no exception. The effects of the pandemic have been felt until now. Following the movement control order (MCO) on March 18, all operations at Syariah courts nationwide have been halted. However, it did not stop the administration of JKSM and the Syariah courts which have continuously discussed, using the online platforms, to formulate reforms if the MCO was finally over. If justice delayed is justice denied, the COVID-19 would seem to be a disaster for our judicial system. But eight months into the crisis, there are signs that what is slowing courts overall is actually accelerating reforms in procedures. This is undoubtedly the hikmah or the positive side of COVID-19. When the pandemic finally ends, we hope that some of the changes that have been introduced will continue to be endured by the Syariah judicial system, and the efforts for reforms will continue. This speech explains the impact of covid-19 pandemic on Syariah judiciary, particularly on its operation and how has the institution, i.e. the Syariah courts dealt with it and the reforms that are taken in making sure the continuity of its service during the pandemic.